2014
DOI: 10.1109/tc.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Processor Instruction Sets from High-Level ISA Specifications

Abstract: As processors continue to get exponentially cheaper for end users following Moore's law, the costs involved in their design keep growing, also at an exponential rate. The reason is ever increasing complexity of processors, which modern EDA tools struggle to keep up with. This paper focuses on the design of Instruction Set Architecture (ISA), a significant part of the whole processor design flow. Optimal design of an instruction set for a particular combination of available hardware resources and software requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Comparison of Parameterized Structures. We compare LESs, CPOGs and CLESs on a number of benchmarks coming from the VLSI design domain, in particular, on-chip communication controllers [7] and processor microarchitectures [8]. We observed that a CPOG often has a lower complexity than a corresponding LES, however, the opposite can also be true.…”
Section: Definitionmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparison of Parameterized Structures. We compare LESs, CPOGs and CLESs on a number of benchmarks coming from the VLSI design domain, in particular, on-chip communication controllers [7] and processor microarchitectures [8]. We observed that a CPOG often has a lower complexity than a corresponding LES, however, the opposite can also be true.…”
Section: Definitionmentioning
confidence: 95%
“…Table 1 provides a summary of our experimental comparison of the complexity of CPOGs, LESs and CLESs. We compressed different sets of partial orders: phase encoders, decision trees, trees of phase encoders, as well as several sets of processor instructions (from ARM Cortex M0 and Intel 8051 processors [8]).…”
Section: Definitionmentioning
confidence: 99%
“…Although proving properties about the hardware implementation is left for future work, the developed infrastructure provides a way to generate testsuites for the processing core from the formal semantics of REDFIN instructions. Furthermore, one can use the semantics to generate parts of the hardware implementation [20] or synthesise efficient instruction subsets [17].…”
Section: Uniform Development Testing and Verification Environmentmentioning
confidence: 99%
“…It has been demonstrated that the FSM and PN formalisms are not well-suited to describing families of many related behaviours [8] and the design methodologies based on them have poor scalability in the context of reconfigurable systems. As an appropriate alternative, the Conditional Partial Order Graph model was introduced by Mokhov et al [8,9]. The model was devised to allow implicit description of families of related behaviours in a compact form as will be demonstrated in Sections 3 and 4.…”
Section: Conditional Partial Order Graphsmentioning
confidence: 99%
“…Once an instruction set is built, it usually undergoes a set of transformations and optimisations which include modification of the set of computational units, changing opcodes of instructions or groups of instructions, modifying the instruction pipeline, etc. Most of these transformations are outside the scope of this work and are defined in [9]. In the following subsections we introduce two new transformaitons.…”
Section: Building Instruction Setsmentioning
confidence: 99%